A Comparative Study of the Effectiveness of Using Padlet in Distance Learning: Viewpoint of Postgraduate Students - Jehad Ali, Al Momani; Ahmad, Abu Musa, Mofeed (Journal of Education and e-Learning Research, 2022)
This study focuses on Padlet and discusses some of the ways in which this web application may be used to facilitate interaction and collaboration in distance learning of Postgraduate students at two Jordanian universities. The use of Padlet is summarized in six domains: research resource gathering, class resources, class diary, FAQ, brain storming and online dialogue. In the spring semester of 2020-2021, the researchers developed an attitude scale that consisted of 20 items. The scale satisfied the validity and reliability tests. A sample of 88 participants from both universities was chosen randomly. The results showed a highly positive attitude towards Padlet as a mobile online interactive and collaborative tool. In addition, the results showed a significant difference in means of the university variables. However, there was no significant difference between the means related to gender. The study recommends training staff members on using Padlet in distance learning sessions to increase interactive and collaborative learning.